Hindgut fermentation of starch is greater for pulse grains than cereal grains in growing pigs. (21st October 2021) - Tan, Felina P Y; Wang, Li Fang; Gao, Jun; Beltranena, Eduardo; Vasanthan, Thava; Zijlstra, Ruurd T
Abstract: The nutritive value of starch, the major source of dietary energy in pigs, varies depending on its susceptibility for digestion. The botanical origin of starch determines starch structure, and therefore, digestibility. To compare digestibility of starch, fiber, gross energy (GE ), crude protein, and amino acid (AA ), and to characterize undigested starch of grains in growing pigs, seven ileal-cannulated barrows (initial body weight, 30 kg) were fed six diets containing 96% of one of six test ingredients (three pulse grains: zero-tannin faba bean, green field pea, or mixed-cultivar chickpea; three cereal grains: hulled barley, hard red spring wheat, or hybrid yellow, dent corn), or a N-free diet in a 7 × 7 Latin square at 2.8 × maintenance digestible energy. Grain samples were ground with a hammer mill through a 2.78-mm screen. Amylose content ranged from 29% to 34% for pulse grains and from 22% to 25% for cereal grains. The apparent ileal digestibility (AID ) of starch was greater ( P < 0.05) in cereal (94% to 97%) than pulse grains (85% to 90%) and was lowest ( P < 0.05) in faba bean (85.3%) followed by field pea (87.2%) and chickpea (90.1%). However, apparent total tract digestibility (ATTD ) of starch of all tested grains was close to 100%. Apparent hindgut fermentability (AHF, as ATTD − AID) of starch was greater ( P < 0.05) in pulse grains (9.9% to 15%) than cereal grains (3.3% to 4.8%). The AHF of total dietary fiber tended to be the greatest ( P < 0.10) for corn (43.5%) and lowest for wheat (25.3%). The AHF of GE was greater ( P < 0.05) in pulse grains (17% to 20%) than in cereal grains (9% to 11%) and resulted in greater ( P < 0.05) digestible energy (DE ) contribution from hindgut fermentation for pulse grains than cereal grains (0.9 vs. 0.5 Mcal/kg). Wheat had the greatest standardized ileal digestibility of total AA (90.2%; P < 0.05). Confocal laser scanning microscopy images revealed that 20% to 30% of starch granules of pulse grains were entrapped in protein matrixes. In scanning electron microscopy images, starch granules were larger in faba bean and field pea than cereal grains. Digesta samples revealed pin holes and surface cracks in starch granules of corn and wheat, respectively. In conclusion, hindgut fermentation of starch and fiber was greater in pulse grains than cereal grains resulting in a greater DE value despite lower ileal DE for pulse grain than cereal grains. Defining the digestible and fermentable fractions of starch may enhance the accuracy of equations to predict the net energy value of these feedstuffs.